Chronic inflammation and progressive calcification as a result of fat necrosis: the worst outcome in fat grafting - Mineda, Kazuhide; Kuno, Shinichiro; Kato, Harunosuke; Kinoshita, Kahori; Doi, Kentaro; Hashimoto, Ichiro; Nakanishi, Hideki; Yoshimura, Kotaro (Plastic and reconstructive surgery (1963), 2014)
Autologous fat injection into the breast has been performed widely for breast augmentation and reconstruction because of recent technical and scientific advancements. However, it is important to learn what occurs and how problematic it can be if fat grafting is not conducted appropriately. Oil cysts were explanted from three subjects who underwent cosmetic fat grafting to the breast 2, 4, and 6 years previously. The oil cyst samples were examined histopathologically. Computed tomographic, magnetic resonance imaging, and mammographic images obtained sequentially after fat grafting were also analyzed. The cyst wall consisted of innermost and outermost fibrous layers and intermediate tissue that contained the regular adipose portion, a degenerated adipose portion, and a fibrous area. Eggshell-like macrocalcifications were seen in the inner surface. Numerous inflammatory cells, mainly MAC2/CD206 anti-inflammatory M2 macrophages, were observed in the degenerated adipose portion. Oil cysts with a longer history showed more calcifications in the innermost layer and a larger fibrous area adjacent to the degenerated fat portion than those with a shorter history. These histopathologic findings and clinical computed tomographic images revealed that oil cysts continued to be inflammatory and calcifications continued to develop over several years. After fat necrosis, long-term chronic inflammation persists and calcification seems to progress without limits. Oil cysts are the worst outcome of fat grafting and must be avoided by standardizing meticulous injection techniques. Therapeutic, V.